Reduced intensity of bone fat exploitation correlates with increased potential access to dairy fats in early Neolithic Europe. (June 2018) - Johnson, Emily V.; Timpson, Adrian; Thomas, Mark G.; Outram, Alan K.
Abstract: Important nutritional resources can be acquired by breaking bone shafts to access marrow, whereas heavy comminution and boiling of cancellous bone is required to extract bone grease. Since labour and fuel costs of these processes differ considerably, the relative intensities of these activities provide a possible proxy for nutritional stress or elevated fat requirements in the context of an overall subsistence strategy. We investigated faunal material from eleven early Neolithic sites in central Europe for bone fracture and fragmentation patterns to ascertain the intensity of bone marrow and grease exploitation. These data indicate that bone grease processing was practised rarely if at all during the early Neolithic, likely made unnecessary by ample access to crop carbohydrates. Bone marrow was exploited at all sites, but with varying intensity that exhibited a significant negative correlation with the proportion of milk-producing domestic ruminants. This observation is consistent with the hypothesis that fats obtained from dairy products reduced requirements for intensive marrow exploitation. Highlights: Bone fracture and fragmentation patterns characterise marrow and grease exploitation. Bone grease exploitation was rare during the early Neolithic of central Europe. In contrast, bone marrow exploitation was commonly practised. The intensity of marrow use negatively correlates with the potential for dairying. The availability of dairy fat likely reduced nutritional reliance on marrow fat.